Physical oceanography from mooring KPO_1095 - Brandt, Peter; Hahn, Johannes; Krahmann, Gerd (PANGAEA, 2020)
GEOMAR moorings are typically equipped with instruments recording pressure, temperature, conductivity, dissolved oxygen and current velocity. Instruments with pressure, temperature, conductivity and oxygen sensors were calibrated in situ immediately prior to and after a mooring deployment period by attaching them to the CTD frame during CTDO casts. Correction terms were then developed from the difference between the sensor readings and the calibrated CTDO data during several minute long calibration stops. These correction terms were then applied to the full deployment periods. This ensured best data quality with recognition of potential sensor drifts and also allowed for the estimation of calibration and measurement errors (Hahn et al. 2014, Bittig et al. 2018, Berx et al. 2019).